Molecular analysis of ethyl methanesulfonate-induced reversion of a chromosomally integrated mutant shuttle vector gene in mammalian cells. - Greenspan, J A (1988)
The molecular mechanisms of ethyl methanesulfonate-induced reversion in mammalian cells were studied by using as a target a gpt gene that was integrated chromosomally as part of a shuttle vector. Murine cells containing mutant gpt genes with single base changes were mutagenized with ethyl methanesulfonate, and revertant colonies were isolated. Ethyl methanesulfonate failed to increase the frequency of revertants for cell lines with mutant gpt genes carrying GC----AT transitions or AT----TA transversions, whereas it increased the frequency 50-fold to greater than 800-fold for cell lines with mutant gpt genes carrying AT----GC transitions and for one cell line with a GC----CG transversion. The gpt genes of 15 independent revertants derived from the ethyl methanesulfonate-revertible cell lines were recovered and sequenced. All revertants derived from cell lines with AT----GC transitions had mutated back to the wild-type gpt sequence via GC----AT transitions at their original sites of mutation. Five of six revertants derived from the cell line carrying a gpt gene with a GC----CG transversion had mutated via GC----AT transition at the site of the original mutation or at the adjacent base in the same triplet; these changes generated non-wild-type DNA sequences that code for non-wild-type amino acids that are apparently compatible with xanthine-guanine phosphoribosyltransferase activity. The sixth revertant had mutated via CG----GC transversion back to the wild-type sequence. The results of this study define certain amino acid substitutions in the xanthine-guanine phosphoribosyltransferase polypeptide that are compatible with enzyme activity. These results also establish mutagen-induced reversion analysis as a sensitive and specific assay for mutagenesis in mammalian cells.